A zinc oxide-modified hydroxyapatite-based cement favored sealing ability in endodontically treated teeth. (September 2019) - Toledano, Manuel; Muñoz-Soto, Esther; Aguilera, Fátima S.; Osorio, Estrella; González-Rodríguez, M. Paloma; Pérez-Álvarez, Mayra C.; Toledano-Osorio, Manuel; Osorio, Raquel
Graphical abstract: Highlights: Oxipatite showed the highest sealing ability of radicular dentin among materials. Oxipatite promoted functional remineralization and low permeability scores. Calcypatite created scarce mineralization and sealing with stress concentration. Abstract: Objectives: To evaluate the effectiveness of different endodontic canal sealers for dentin permeability reduction and to determine the viscoelastic performance of root dentin after their application. Methods: Cervical, medial and apical root dentin surfaces were treated with two experimental hydroxyapatite-based cements, containing sodium hydroxide (calcypatite) or zinc oxide (oxipatite); an epoxy resin- based canal sealer, AH Plus; and gutta-percha. Root dentin was evaluated for fluid filtration. Field emission scanning electron microscopy, energy dispersive analysis, AFM, Young's modulus and Nano-DMA analysis were also performed, at the inner and outer zones of dentin. Results: Dentin treated with oxipatite showed the lowest microleakage among groups with hermetically sealed tubules and zinc-based salt formations. Samples treated with oxipatite showed the highest Ei at the cervical dentin third among groups, at 6 m of storage. Oxipatite promoted the highest complex modulus and tan delta values at the inner zone of both cervical and medial root dentin. Calcypatite favored the lowest tan delta outcomes at the inner zone of apical dentin at 6 m. Conclusions: Specimens treated with oxipatite showed the highest sealing ability, based on the highest Young's modulus and dentin mineralization, achieved by closing dentinal tubules, voids and pores that reinforced the inner zone of root dentin. The homogeneity of viscoelastic properties among the different root dentin thirds favored the energy dissipation without creating zones of stress concentration and micro-cracking which would have challenge micropermeability. Thereby, among the tested materials oxipatite is proposed as canal filling material and sealer in endodontics. Clinical significance: Oxipatite could be considered a good candidate for root canal filling material and sealer due to its improved long-term sealing ability and to the advanced remineralization, and so to the enhanced energy dissipation achieved at the inner zone of the radicular dentin.